Pengembangan Keamanan Dan Jaringan Pada System Windows Mengunakan Metode Hardening (Studi Kasus : PT. Shiva Shakti Steel) - Moh. Triyana Abbas; Taswanda Taryo; Murni Handayani (OKTAL : Jurnal Ilmu Komputer dan Sains, 2022)
In the current digital era, security and network are very important in a system to support all activities in the world of work, especially for offices. In this case the windows system at PT. Shiva Shakti Steel is currently still slow, supporting application performance feels slow, and network security is still vulnerable. PT. Shiva Shakti Steel is a company that uses technology and information, using the internet network on a windows system, which is expected to help management to process and present data and information effectively, quickly, and accurately. The purpose of his research is expected to accelerate the performance of the windows system, supporting applications and network security. In this study, the data analysis technique that the researcher uses is the hardening system method. Hardening system refers to providing various means of protection in a computer system. Protection is provided in multiple layers, and is often referred to as deep defense. Protecting in layers means protecting at host level, application level, operating system level. According to John D. Howard in his book "An Analysis of security incidents on the internet" states that: "Computer security is a preventive measure from attacks by computer users or irresponsible network accessors". Meanwhile, according to Gollmann in 1999 in his book "Computer Security" states that: "Computer security is related to selfprevention and detection of unrecognized intruders in computer systems". From the results of the analysis of vulnerability testing carried out, namely testing system and network security on windows systems using the hardening method at PT. Shiva Shakti Steel, it can be concluded that the hardening system method was chosen because this is the initial foundation for the system, so that it can solve some of the problems that exist in the system.